The Influence of Future-Oriented Technology Analysis: Addressing the Cassandra Challenge - Ron Johnston (Foresight and STI Governance)
Rapidly changing context as well as growing uncertainty in almost all spheres of life lead to an understanding that standard means are not applicable to solving emerging complex issues. The ability to anticipate major emerging challenges is more relevant than ever before. Renowned international institutions constantly inform on coming challenges and threats, however, the topic of futures research does not receive proper attention. The paper examines why despite evident seriousness of the situation future studies are not in relevant demand and provides a detailed explanation. The author provides examples of the Foresight practices that had significant or in contrast few impact on decision making in various countries. The study is based on interviews with the participants of the International Conference "Future-Oriented Technology Analysis" (FTA). The answers illustrated the present state of FTA, its objectives and the vector. Analysis of expert opinions leads to the following conclusions. Poorly developed partnerships have a negative influence on the use and development of the FTA. Most managers are not familiar with these tools and their capabilities. There is deeply rooted opinion that unforeseen events will always occur, and there are inevitable limitations to any attempt to influence the future, and therefore the ability to change anything is minuscule. This belief only strengthens the current trend. In many countries, government officials have been largely resistant to the concept and the value of FTA. It does not fit easily with established public administration procedures and protocols. This situation has several explanations: the universities have no educational programs on FTA; managers lack the knowledge and skills to foresee serious challenges. In addition there is a lack of a reliable method enabling to assess FTA mechanisms and prove its effectiveness. The challenge for high impact FTA is to select issues that not necessarily have long time horizon, but rather are relevant and bottom-line. Special education and training in this field are needed. Therefore, a key challenge for the next generation of FTA projects is to shift focus from expertise building to rooting recognition of importance of FTA learning among non-specialists. This presumes the introduction of special issues into the curricula of schools and universities, as well as training of public officers.